Low Literacy of Sejarah Kampung Among Generation Alpha and its Solutions - Wilaela Wilaela; Usman Usman; Widiarto Widiarto (Tarikhuna: Journal of History and History Education, 2025)
This article explains the low literacy of Alpha generation children regarding the Sejarah Kampung or the local history where they live. This qualitative research took cases in the community of RW 3, Maharatu, Marpoyan Damai Pekanbaru. Purposively, 14 informants were identified as children aged 11-14 years at primary and junior high school levels and five informants were figures related to literacy activities. The research found that these children, at home or school, never received stories about history or important stories in their village. Their historical awareness does not emerge and character education becomes increasingly difficult. The internal-external factors include the loss of the habit of telling stories due to the death of community leaders and elders, economic limitations which make parents busy earning a living; and the culture of using cellphones, television and other technological and telecommunications equipment has taken over the focus of children's attention. Stories about the Sejarah Kampung are not interesting, and parents and teachers never tell them. The solution to increasing Sejarah Kampung literacy among the Alpha generation is to provide space for integrative learning of local history with other subjects, which can be carried out using varied methods, such as collaboration between schools, history observer communities, and parents. The local history is presented through educational tourism and utilizing social media platforms and other digital forms, adapting to the tendencies of the Alpha generation.